Endoplasmic Reticulum-Vacuole Contact Sites "Bloom" With Stress-Induced Lipid Droplets. (March 2018) - Henne, W. Mike; Hariri, Hanaa
Lipid droplets (LDs) serve as specialized cytoplasmic organelles that harbor energy-rich lipids for long-term storage and may be mobilized as nutrient sources during extended starvation. How cells coordinate LD biogenesis and utilization in response to fluctuations in nutrient availability remains poorly understood. Here, we discuss our recent work revealing how yeast spatially organize LD budding at organelle contacts formed between the endoplasmic reticulum and yeast vacuole/lysosome (sites known as nucleus-vacuole junctions [NVJs]). During times of imminent nutrient exhaustion, we observe blooms of stress-induced LDs surrounding the NVJ and find that this LD clustering is regulated by NVJ-resident protein Mdm1. We also discuss several emerging studies revealing specific proteins that demarcate a subpopulation of NVJ-associated LDs. Collectively, these studies reveal a previously unappreciated role for the spatial compartmentalization of LDs at organelle contacts and highlight an important role for interorganellar cross talk in LD dynamics under times of nutritional stress.